2003
DOI: 10.1212/01.wnl.0000039067.80149.03
|View full text |Cite
|
Sign up to set email alerts
|

Hyperventilation-induced limb shaking TIA in Moyamoya disease

Abstract: The authors present a case of hyperventilation-induced left upper limb shaking from an underlying Moyamoya disease. Video EEG monitoring and SPECT study were performed. Leptomeningeal collateral circulation was investigated by conventional angiography and by SPECT study with acetazolamide. Limb shaking in Moyamoya disease may result from a transient hypoperfusion of the contralateral frontoparietal cortex rather than basal ganglia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 11 publications
1
32
1
1
Order By: Relevance
“…We found 38 patients in 27 studies (Supporting Information Table 1),2–28 including 2 patients we previously reported 10, 26. We also found 4 new patients in our medical records from 1985 to 2008.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…We found 38 patients in 27 studies (Supporting Information Table 1),2–28 including 2 patients we previously reported 10, 26. We also found 4 new patients in our medical records from 1985 to 2008.…”
Section: Resultssupporting
confidence: 54%
“…The remaining patient had Graves' disease and improved after thyroidectomy 27. In 7 of the 42 patients, the term “dyskinesia” was used for the description of the movement disorders 19–21, 26. All 7 patients suddenly developed dyskinesia repeatedly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar case of singing-induced choreatic movements in a moyamoya patient from Korea has recently been reported [16]. Hyperventilation-induced limb-shaking transient ischaemic attacks have also been attributed to a similar pathogenic mechanism, which however caused hypoperfusion of the frontoparietal cerebral cortex in a Korean patient with moyamoya disease [17].…”
Section: Discussionmentioning
confidence: 74%
“…Limb-shaking TIA has been explained by the ''hypoperfusion theory'', in which carotid stenosis may lead to decrease in cerebral blood flow in critical watershed territories in some situations, especially the dorsolateral frontal cortex [15]. Ischemic damage to the neurons may increase membrane instability, excitatory neurotransmitter release, neuronal excitability, and consequent movement disorders [16].…”
Section: Discussionmentioning
confidence: 99%